2010
DOI: 10.1038/jcbfm.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor Class-A Has a Central Role in Cerebral Ischemia–Reperfusion Injury

Abstract: The innate immune response is involved in the pathophysiology of cerebral ischemia-reperfusion (I/R) injury. Recent evidence suggests that scavenger receptors have a role in the induction of innate immunity. In this study, we examined the role of scavenger receptor A (SR-A) in focal cerebral I/R injury. Both SR-A À/À mice (n = 10) and age-matched wild-type (WT) mice (n = 9) were subjected to focal cerebral ischemia (60 minutes), followed by reperfusion (for 24 hours). Infarct size was determined by TTC (triphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 44 publications
(135 reference statements)
1
52
0
Order By: Relevance
“…Interestingly, either deficiency of TLR4 (27,73,74) or TLR2 (101) protected the brain from cerebral I/R injury. Similar observations have been found in either CD36 (33,89,96) or SR-A knockout mice (112). Deficiency of either CD36 (33, 89, 96) or SR-A (112) protects the brain from cerebral I/R injury.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, either deficiency of TLR4 (27,73,74) or TLR2 (101) protected the brain from cerebral I/R injury. Similar observations have been found in either CD36 (33,89,96) or SR-A knockout mice (112). Deficiency of either CD36 (33, 89, 96) or SR-A (112) protects the brain from cerebral I/R injury.…”
Section: Discussionsupporting
confidence: 77%
“…Studies of SR-A −/− mice have shown that SR-A enhances the pathogenesis of diabetic nephropathy [42], pulmonary Mycobacterium tuberculosis infection [43], cerebral ischemia-reperfusion injury [44], and the development of colitis and Alzheimer disease [16,17,45], and SR-A-positive macrophages play a pivotal role in the progression of ovarian and prostate cancers [14,15]. Thus, our finding of IMD downregulating SR-A expression may be helpful in treating these diseases.…”
Section: Discussionmentioning
confidence: 91%
“…While there are differences in the experimental models employed by Xu 111 and Lu 112 both studies led to the same conclusion: SR-A contributes to brain injury after ischemia and/or reperfusion. In support of this concept, Murgas et al used SR-A −/− astrocytes in vitro to demonstrate that the presence of SR-A contributes to the neuro-inflammatory response (Table 3).…”
Section: Sr-a Functions In Multiple Diseases and Organ Systemsmentioning
confidence: 91%
“…112 After 60 minutes of occlusion, the blockage was removed and reperfusion allowed for varying periods of time. SR-A −/− mice showed less cerebral damage (smaller infarct size) after ischemia and decreased cerebral and systemic inflammatory response when compared with WT mice with cerebral ischemia/reperfusion.…”
Section: Sr-a Functions In Multiple Diseases and Organ Systemsmentioning
confidence: 99%